The Validity and Practical Test of STEM@Home Learning Design to Empower Student's Science Literacy - Ramli, Murni; Novalya, Astrid Dyah; Indriyanti, Nurma Yunita; Wichaidit, Sittichai; Wichaidit, Patcharee Rompayom (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2024)
The science, technology, engineering, and mathematics (STEM) approach is one of the approaches to teaching integrative science contextually and to promote science literacy, which is identified to remain low among Indonesian students. Applying STEM projects to grade 8 students has been challenging during the pandemic. Thus, there is a need to develop an online STEM project that accommodates learning at home or distance learning, is suitable during the pandemic, and incorporates training to improve science literacy. Therefore, we developed a STEM@Home Learning Design by adopting the Flower STEM-Approach Design using the topic of vibration, wave, and sound. This study aims to reveal the validity of the learning design by involving 44 reviewers (lecturers and teachers), followed by the practical test run by 117 reviewers of lecturers, teachers, and student teachers majoring in science education. A questionnaire consisting of 30 items on learning design, instructional setup, and student competencies was distributed online. On average, the respondents scored 4 to 5 on a 5-point scale of the STEM@Home Learning Design in each indicator (86.3%). It can be concluded that the STEM@Home Learning Design is feasible to proceed to the empirical study.